Smart Pond for Smart Aquaculture: Sebagai Solusi Kualitas Air di Lahan Budidaya untuk Menunjang Industri 4.0 yang Terintegrasi dengan Smartphone - Rarassari, Madyasta A.; Parlindungan, Anders; Moethia, S.; Oktavia, V. (Seminar Nasional Lahan Suboptimal, 2019)
Rarassari MA, Parlindungan A, Moethia S, Oktavia V. 2019.  Smart Pond for Smart Aquaculture : as a water quality solution in cultivated land to support indonesia 4.0 which is intergrated with smartphone. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 546-553. Palembang: Unsri Press.Water quality in Aquaculture ponds is important to knows. One of the physical parameters of water quality are acidity (pH), dissolved oxygen (DO) and temperature. Changes of physical parameters effect the growth and endurance of fish that are cultivated. Water quality sometimes experiences water changes in water which cause a decrease in water quality, so it’s necessary to do good water quality management where it requires the presence of regular fish farmers in the cultivation pond. In this case an idea was made with technology to properly monitor the quality of aquaculture’s pond based on Smartphone with GSM network. The mechanism on smartphone is an application to improve the quality of aquaculture’s pond. Routinely smartphone’s remote devices measure physical parameters in the form of acidity (pH), dissolved oxygen (Do) and temperature. The aims of this idea is that fish farmers can move quickly, righly and efficiency in the time management of the technology.Keywords: acidity (pH), dissolved oxygen (DO), smart aquaculture, temperature, water quality